Current topics in complement - Lambris, John D. (Advances in experimental medicine and biology, 2006)
The Third Aegean Conferences Workshop on Complement-Associated Diseases, Animal Models, and Therapeutics convened to discuss progress in complement research as it pertains to human disease pathogenesis and therapeutics. The rapid pace of research and new experimental approaches allow an integrated view of the in vivo biology of the complement system. This book collects writings on the functions of complement, pathophysiology, protein structures, design of complement inhibitors, and complement assays discussed at the conference.